Personalized learning environment based on cognitive styles for mental model development in learning chemical bonding - Abd. Halim, Noor Dayana (2012)
The purpose of this research is to develop a personalized learning materials based on students’ preferences in cognitive style, which are Field Dependent (FD) and Field Independent (FI), in learning chemical bonds. The learning materials were designed and developed based on the characteristics of the cognitive styles and further integrated in the website. The effect of the website was investigated in order to promote students’ achievements, students’ mental model developments and their pattern of interaction while learning using the website. The pattern of interaction focused on five types of interaction, which are learner-instructor, learner-self, learner-learner, learner-content and learner-interface interaction. The research samples consist of Form 4 students from a school located in Johor Bahru. A combination of qualitative and quantitative methods has been employed in data collection and analyzing the research data. The findings show that students had a positive improvement in their achievement in learning chemical bonds. Beside, students had also developed a scientific mental model after learning using the website. Besides this, students categorized under FD showed the highest total hit of interaction and enjoyed using all the applications provided on the website as compared to FI students. This showed that the FD students were more active and socially orientated while learning using the website as compared to FI students. However, both types of students showed positive improvement in their achievement and in their mental model development. In conclusion, the focus on emphasising individual differences to promote students’ learning is a vital factor to be considered, as this aspect proves valuable for both students and teachers